Neutron shielding of EPDM rubber with boric acid: Mechanical, thermal properties and neutron absorption tests. (May 2016) - Özdemir, T.; Akbay, İ.K. and Uzun, H. and Reyhancan, İ.A.
Abstract: It is well known that the materials with boron content are very effective in thermal neutron absorption and high hydrogen content is also a desirable case for the thermal neutron shielding. Ethylene Propylene Diene Termonomer (EPDM) rubber is a good candidate material for neutron shielding due to its hydrogen content. In this study, EPDM rubber with boric acid was prepared and thermal and mechanical tests were carried out and the changes in the thermal and mechanical properties were studied, explicitly. Moreover, vulcanization kinetics was investigated in order to understand the change in the vulcanization behaviour with the boric acid addition. Microwave assisted sol–gel analysis and conventional Soxhlet extraction tests were completed to determine the gel content of the polymer composite. Theoretical and experimental neutron absorption test results were compared and the results have shown and that they were comparable with each other. It was concluded that EPDM with boric acid is an effective neutron moderating material. Highlights: Boric acid is a good neutron absorber used as neutron poison for the fission reactions. EPDM has inherent high hydrogen content. EPDM with boric acid content would lead a good neutron absorption. The neutron absorber designed is inexpensive and have a flexible nature.